2019
DOI: 10.1242/jeb.210534
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the effect of food availability, growth and host condition on disease susceptibility in a marine invertebrate

Abstract: Food provisioning influences disease risk and outcome in animal populations in two ways. On the one hand, unrestricted food supply improves the physiological condition of the host and lowers its susceptibility to infectious disease, reflecting a trade-off between immunity and other fitness-related functions. On the other hand, food scarcity limits the resources available to the pathogen and slows the growth and metabolism of the host on which the pathogen depends to proliferate. Here, we investigated how food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Interestingly, interplays between metabolic reprogramming and immunity have been evidenced as an ancestral principle that could support innate immune priming in very distant organisms such as C. elegans and mammals (51,57). Previous studies have also already emphasized the potential trade-offs linked to innate immune priming notably on reproduction potential (58)(59)(60) but also between immunity and physiological status in the oyster (61). Interestingly, we observed that the elevated immune baseline in long-term priming did not systematically result in a strong secondary response when facing viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, interplays between metabolic reprogramming and immunity have been evidenced as an ancestral principle that could support innate immune priming in very distant organisms such as C. elegans and mammals (51,57). Previous studies have also already emphasized the potential trade-offs linked to innate immune priming notably on reproduction potential (58)(59)(60) but also between immunity and physiological status in the oyster (61). Interestingly, we observed that the elevated immune baseline in long-term priming did not systematically result in a strong secondary response when facing viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although food availability generally improves the physiological condition of the host and lowers their susceptibility to infectious disease, reflecting a tradeoff between immunity and other functions 37,38 , food scarcity can limit the resources available to the pathogen and slow the growth and metabolism of the host on which the pathogen depends to proliferate [39][40][41] . In the context of oyster-OsHV-1 interaction, greater food availability favors the acquisition of energy reserves but overall increases mortality risk by increasing the growth and metabolism of the host 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The farmed oyster Crassostrea gigas is heavily affected by the Pacific Oyster Mortality Syndrome (POMS) targeting juveniles (Barbosa Solomieu et al, 2015;Pernet et al, 2016). This disease is multifactorial and depends on water temperature (Petton et al, 2015), development stage (AzĂ©ma et al, 2017), and oyster diet (Pernet et al, 2019). It is also polymicrobial due to the combined development of viral and bacterial infections (de Lorgeril et al, 2018).…”
Section: Introductionmentioning
confidence: 99%